Temporal goal scoring characteristics in elite Brazilian football: a longitudinal study - De Sousa Pinheiro, Guilherme (2023)
This study aimed to investigate the temporal pattern of goal scoring in recent 8 editions of the elite Brazilian Championship. The sample consisted of 3,039 matches (7,170 goals) from the seasons 2012 to 2019 of the 1st division of the Brazilian Championship. The official match reports, which are publicly available on the website of the Brazilian Football Confederation - CBF (www.cbf.com.br), were analyzed. Data collection occurred through the observational methodology. Two experienced observers registered the data. Inter and intra-rater reliability was calculated to guarantee the quality of the observation system. During the 2012-2019 seasons an average of 393.50 goals occurred in the 1st half, and 502.75 in the 2nd half. The average number of goals per match was 2.36. Results indicated a higher incidence of goals scored in the 2nd half of the match (p < 0.05). An upward trend in the number of goals scored was observed as match-play time progressed. Football coaches and practitioners may plan and practice match strategies more effectively according to the time trend of goals in a match.